A STUDY OF PARENTS' PREFERENCES IN MASALLE VILLAGE FOR FORMAL EDUCATION IN PUBLIC SCHOOLS COMPARED TO ISLAMIC BOARDING SCHOOLS - Riyo Asmin Syaifin (IAI DDI Mangkoso, 2025)
Formal education in public schools is preferred by parents in Masalle Village as a means of education for their children. Public school education offers a broader education that focuses on an academic curriculum designed to equip children with real knowledge and skills in various fields, but religious education in public schools is very limited compared to Islamic boarding schools. Alumni of pesantren generally show better character and manners than public school graduates.This study aims to examine parents' preferences in Masalle village in choosing formal education in public schools over pesantren. The main focus of this research is to understand the factors that influence parents' decisions in determining the type of education considered most suitable for their children. The research approach used is a qualitative method with data collection techniques through in-depth interviews, observation and documentation.The results show that parents' preferences are influenced by several factors, including parents' educational background, family economic conditions, accessibility of education, and their views on the quality of religious and academic education. Most parents who choose public schools consider the academic curriculum to be superior and the wider career opportunities in the future. Meanwhile, parents who chose pesantren emphasized the importance of religious education as a moral foundation for their children.